Dual Pathways to Performance in Manufacturing Companies: Rethinking Competency, Culture, and Job Satisfaction - Asmini, Asmini; Adawiah, Andi; yusuf, Andi Muhammad (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2026)
This study aims to examine the effects of competency and organizational culture on employee performance, with job satisfaction as a mediating mechanism. It advances a novel claim that competency operates through dual pathways, directly enhancing performance while indirectly shaping outcomes via job satisfaction, whereas organizational culture follows a predominantly direct route. Using a quantitative associative design, data were collected from 250 employees from manufacturing companies and analyzed with PLS-SEM to assess relationships among latent constructs. The results show that competency significantly improves job satisfaction and performance, while organizational culture does not affect job satisfaction but directly enhances performance. Mediation analysis confirms that job satisfaction partially mediates the competency–performance relationship but not the organizational culture–performance link. These findings imply that organizations should prioritize competency development as a leverage point for both satisfaction and performance, while positioning culture as a direct performance driver.